ANTIOXIDANT ACTIVITY OF GUMMY CANDIES OF PURPLE NUTSEDGE TUBER (Cyperus rotundus L.) AND CINNAMON (Cinnamomum burmannii Nees ex & T. Nees Blume.) EXTRACTS - Tolkhah, Ronal; Purwasih, Ratih; Oktavia, Nabiilah (Jurnal Jamu Kusuma, 2024)
Along with the development era, health is increasingly being considered. One of the things that is currently being discussed is functional food containing antioxidant compound that can inhibited free radical that cause cardiovascular disease from plant extracts. One of the plants that contains antioxidants is purple nutsedge tuber (Cyperus rotundus L.). Gummy candies have characteristics with a dense and chewy gel texture. The combination with cinnamon (Cinnamomum burmannii Nees ex & T. Nees Blume) is done to increase the antioxidant value. This study aims to determine the antioxidant activity in gummy candies, which are produced using a combination of purple nutsedge tuber and cinnamon extracts. This study employed a quantitative-descriptive methodology. The formulation of the gummy candies was prepared with a ratio of purple nutsedge tubers to cinnamon, F1(15:5%), F2(10:10%), and F3(5:15%). The organoleptic of the gummy candies were a dark brown color, a distinctive aroma associated with purple nutsedge tubers, sweet and astringency, and a chewy texture. The moisture content of the gummy candies in the F0-F3 were 12.430-15.593% and the ash content were 0.131-0.265%. Both parameters which met the requirements of SNI 3547.2:2008. The antioxidant activity of the purple nutsedge tuber extract was 65.675 ppm, while the cinnamon extract was 44.883 ppm. The antioxidant activity on gummy candies from F0-F3 with IC50, respectively, amounted to 176.046 ppm, 121.184 ppm, 84.178 ppm, and 73.145 ppm, with weak to strong categories. It was observed that as the quantity of cinnamon extract incorporated into the formulation increased, the antioxidant activity also increased.